The Ants Go Marching: Interns’ and Librarians’ Roles in a Global Collaboration. - Barr, Dorothy (Issues in Science and Technology Librarianship, 2014)
AntWiki was created "to provide a wealth of information on the world's ants." The wiki gathers contributions from ant experts worldwide and makes the information accessible to anyone with an Internet connection. Part of AntWiki began as the Global Ant Project, GAP, an online bibliography designed to bring together the work of ant taxonomists past and present, with brief biographies and also pictures of each scientist whenever available. This paper describes how five Simmons College Graduate School of Library & Information Science (GSLIS) students worked on GAP and AntWiki, finding and collecting PDFs of articles; posting online those that are out of copyright; searching for and uploading portraits of taxonomists; and creating a page on Antwiki on Human Culture and Ants. The project thus became a collaboration of researchers, librarians and library students to further the world's knowledge of ants, the "little creatures that run the world" in E.O. Wilson's words (Upton 1995). [ABSTRACT FROM AUTHOR]